2017
DOI: 10.3382/ps/pew432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary methionine on growth performance, meat quality and oxidative status of breast muscle in fast- and slow-growing broilers

Abstract: This experiment was conducted to investigate the effects of dietary methionine (Met) on growth performance, carcass traits, meat quality and oxidative status of breast muscle in fast- (Arbor Acres, AA) and slow- (Partridge Shank, PS) growing broilers from 1 to 42 d of age. The broilers were divided into a 2 × 3 factorial design with 6 replicates per treatment. Diets were formulated to contain low (LM, 0.35 and 0.31% during 1 to 21 and 22 to 42 d), adequate (AM, 0.50 and 0.44%) and high (HM, 0.65 and 0.57%) Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…At the molecular level, the lower glycogen content could be explained by the higher phosphorylation of the α-catalytic subunit of AMPK, which inhibits glycogen synthesis by phosphorylating the glycogen synthase [ 112 ]. Recently, Wen et al [ 113 ] reported that low levels of dietary methionine negatively affect growth performance, carcass traits, meat quality attributes and oxidative status of breast muscle in a strain-dependent manner (fast- vs. slow-growing broiler chickens). However, no further investigation regarding the effect of the bird genotypes on the response to dietary methionine has been conducted in the study [ 113 ].…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, the lower glycogen content could be explained by the higher phosphorylation of the α-catalytic subunit of AMPK, which inhibits glycogen synthesis by phosphorylating the glycogen synthase [ 112 ]. Recently, Wen et al [ 113 ] reported that low levels of dietary methionine negatively affect growth performance, carcass traits, meat quality attributes and oxidative status of breast muscle in a strain-dependent manner (fast- vs. slow-growing broiler chickens). However, no further investigation regarding the effect of the bird genotypes on the response to dietary methionine has been conducted in the study [ 113 ].…”
Section: Nutritionmentioning
confidence: 99%
“…Recently, Wen et al [ 113 ] reported that low levels of dietary methionine negatively affect growth performance, carcass traits, meat quality attributes and oxidative status of breast muscle in a strain-dependent manner (fast- vs. slow-growing broiler chickens). However, no further investigation regarding the effect of the bird genotypes on the response to dietary methionine has been conducted in the study [ 113 ].…”
Section: Nutritionmentioning
confidence: 99%
“…Moreover, this supplementation is proven to have an expected effect in nonruminant animals. Methionine and lysine, as the first and second limiting amino acids, respectively, were reported to enhance the growth rate and carcass yield and slightly improve meat quality by decreasing the rate of protein denaturation and contributing to the tenderness of chicken breast meat [2]. Furthermore, methionine in the rumen-protected form is considered to be capable of supporting protein synthesis and inhibiting protein degradation through involvement in the synthesis of reduced glutathione (GSH), which naturally inhibits reactive oxidative species (ROS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In breast muscle, the contents of crude ash, moisture or crude protein were not affected by different methionine levels. However, birds fed the low methionine diets had the highest content of ether extract in among all the treatments (p < 0.05) [42]. Means in the same row within each classification bearing different letters are significantly (p ≤ 0.05) different.…”
Section: Meat Compositionmentioning
confidence: 91%